Research on Digital Technology of Paleontological Skeletal Specimens and Its Application in Museum Display - Qi, Ruize (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Digital technology plays an increasingly important role in the display of paleontological skeletal specimens. Through technologies such as high-precision scanning and virtual reality, viewers can immerse themselves in the living environment of ancient organisms and experience unprecedented interaction. In this process, there are also technical challenges, such as the fragility of specimens, the balance between scientific and educational display content, and so on. In order to fully leverage the advantages of digital technology, museums need to strengthen technological research and innovation, enhance audience education and guidance, and focus on cross platform cooperation and intelligent management. In the future, with the continuous advancement of technology, personalized and customized display experiences will become possible, bringing audiences richer and more vivid knowledge of paleontology. The application of digital technology not only enhances the display effect of paleontological specimens, but also injects new vitality into paleontological research and knowledge dissemination. Thoroughly studying the digital technology of paleontological skeletal specimens and its application in museum exhibitions is of great significance for promoting the development of paleontological research and enhancing public scientific literacy.